Kajian komparatif perancangan dan produksi peralatan saji (Studi kasus CV Estetika Indonesia) - Hafshoh Musfiroh (Institut Seni Indonesia Yogyakarta, 2020)
The purpose of this study was to find out: (1) Comparison of the process of designing and producing serving serveware from wood and clay materials in CV Estetika Indonesia. (2) Types of food serveware products at CV Aesthetic Indonesia. (3) Comparison of design aspects of food and wood products from clay in CV Estetika Indonesia. This research was carried out at CV Estetika Indonesia and wood suppliers in Putat Wetan Village and Clay suppliers in Melikan Village, Klaten from 10 May to 10 June 2019. This study used a descriptive comparative method with a qualitative approach. The data used in this study are qualitative data with data sources in the form of informants, documents, observations, interviews, and documentation. Based on the results of the study it can be concluded: (1) The process of designing design serveware at CV Estetika Indonesia refers to the briefs given by the buyer. The process of designing food serveware products with wood material is carried out with machines so that it is more in line with the concept of the mass product or industrial products. While clay products are more directed at handicrafts because the products are produced manually using hands. (2) Types of fast food products CV Aesthetics of wood and clay materials include trays (tray), plates (cutting board), bowls (bowls), plates (plates), glass (glass), and coasters (coasters). (3) Design comparisons of serving serveware products include the design process, style and theme, finishing, color, ergonomics, and packaging.